Innate Immunity Stimulation during the COVID-19 Pandemic: Challenge by Parvulan - Beniamino Palmieri; Antonio Manenti; Francesca Galotti; Maria Vadalà (Journal of Immunology Research)
Aim. We report an open spontaneous anecdotical retrospective survey of Corynebacterium parvum administration to 4000 fragile immune-depressed and multimorbid patients treated with a killed C. parvum strain to enhance innate immunity, integrating the adaptative immune response for long-standing antinfectious resistance. Methods. A total of 4000 patients (1900 men and 2100 women) with mild, moderate, or chronic disease, appealing to our Second Opinion Medical Consultation Network, signed an informed consent form and were injected subcutaneously with C. parvum. The treatment was followed up to 6 months, completing the short form of the medical outcome health survey questionnaire (SF-36) directly by the patients or their parents and monitoring their health status regularly via telemedicine (Skype, WhatsApp, mail, etc.) or outpatients visits. Results. The main efficacy endpoints, as assessed by the SF-36 questionnaire are: significant improvements in the mental and physical role functioning score (p<0.02), better general health; social role performance (p<0.02), vitality (p<0.03), and a significant pain reduction (p<0.03). A quick (48-72 hours) symptoms improvement and/or complete regression of the herpetic eruptions was observed in 1000 affected patients with disappearance or relieve of herpetic neuralgia (reduced in 80% of cases); also full recovery or frequency reduction (30%) of recurrent cystitis and prostatitis in 120 affected patients. Last but not least, a life quality improvement in 100 oncologic patients of overall 200 cases. A significant increase in the lymphocyte count (p<0.01), mainly helper and killer lymphocytes, was noted 6 months after Parvulan injection vs. the baseline. The asymptomatic SARS-CoV-2 patients who were incidentally enrolled in our survey were tested at the sixth month for antibodies against SARS-CoV-2, and 14 patients had high levels of SARS-CoV-2 antibodies. The incubating COVID infections of the Parvulan-injected patients even if frail and multimorbid recovered in short term (48-96 hours) with a benign clinical course, without need of drugs administration except for the variants, such as Delta and Omicron, whose infections lasted on average one week and required some antipyretics and low-dose steroids for a few days. Conclusions. Our results confirm that C. parvum is quite safe and effective in supporting immune-compromised patients when epidemic or pandemic events increase the life risk and any kind of infection and complication rate. Further double-blind placebo evidence-based studies are urgently required, and our numerically substantial not sponsored spontaneous observation is exclusively intended to promote further evidence-based double-blind institutional studies.